Hubungan Stress Kerja Dengan Kepuasan Kerja Pada Pegawai Negeri Sipil Di Agraria Dan Tata Ruang/Badan Pertahanan Nasional Kota Tebing Tinggi - Habeahan, Andrias; Rysidah, Rysidah (Universitas Medan Area, 2024)
This article aims to determine the correlation between Job Stress and Job Satisfaction in Civil Servants in Agrarian and Spatial Planning/National Defense Agency (ATR/BPN) Tebing Tinggi City. The scale used in this study is the scale of job stress job satisfaction where the subjects in this study were Civil Servants in Agrarian and Spatial Planning/National Defense Agency (ATR/BPN) Tebing Tinggi City, totaling 44 people. The data analysis method used in this study is Product Moment correlation, so the following results can be obtained: there is a significant negative relationship between job stress and job satisfaction. The results are proven by the correlation rxy = -0.482; P = 0.001 90 where the difference between the two means exceeds SD number = 10.417 and job satisfaction in Agrarian and Spatial Planning/ The National Defense Agency (ATR/BPN) of Tebing Tinggi City is classified as moderate with an empirical mean of 134.00 hypothetical mean = 137.5 where the difference between the two means exc eeds the SD number =21.884.